PERAN KOMODITAS PADI SAWAH DALAM PEMBANGUNAN DAERAH DI KABUPATEN CILACAP - Irene kartika eka wijayanti; Okki Nur Safitri; Djeimy Kusnaman; Altri Mulyani (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
The primary purpose of this research is to evaluate Cilacap Regency's lowland rice production system. The second step is to examine the features of lowland rice commodity distribution in Cilacap Regency based on locality and specialization and to understand how lowland rice functions as a sector base to support the operations of the food crop agriculture sector in Cilacap Regency. This research employs a qualitative descriptive methodology with secondary data types based on Central Statistics Agency (BPS) documentation for the years 2014–2019. Excel 2010 is used to process secondary data. The output of lowland rice from 2014 to 2019 was the subject of the study. The location quotient (LQ) analysis, locality and specialization analysis, basic service ratio analysis (BSR), and regional multiplier are all used in the data analysis process (RM). The results revealed that the districts of Dayeuhluhur, Wanareja, Majenang, Kedungreja, Patimuan, Bantarsari, Kampung Laut, Adipala, Maos, Sampang, Kroya, Binangun, and Nusawungu were the primary areas for lowland rice commodities in Cilacap Regency from 2014 to 2019. Second, there are no sub-districts in Cilacap Regency that are exclusively focused on lowland rice commodities and the features of the distribution of lowland rice commodities are not concentrated in one sub-district. Third, Cilacap Regency's agricultural activities might be supported by the lowland rice commodity base sector from 2014 to 2019.